A Clustering based Feature Selection Approach using Maximum Spanning Tree - Tarek, Md Hasan; Akhter, Suravi; Ahmed, Sumon; Islam, Md Shariful; Shoyaib, Mohammad; Begum, Zerina (Dhaka University Journal of Applied Science and Engineering, 2023)
Mutual information (MI) based feature selection methods are getting popular as its ability to capture the nonlinear and linear relationship among random variables and thus it performs better in different fields of machine learning. Traditional MI based feature selection algorithms use different techniques to find out the joint performance of features and select the relevant features among them. However, to do this, in many cases, they might incorporate redundant features. To solve these issues, we propose a feature selection method, namely Clustering based Feature Selection (CbFS), to cluster the features in such a way so that redundant and complementary features are grouped in the same cluster. Then, a subset of representative features is selected from each cluster. Experimental results of CbFS and four state-of-the-art methods are reported to measure the excellency of CbFS over twenty benchmark UCI datasets and three renowned network intrusion datasets. It shows that CbFS performs better than the comparative methods in terms of accuracy and performs better in identifying attack or normal instances in security datasets. DUJASE Vol. 7 (2) 47-55, 2022 (July)